Unraveling the venom chemistry with evidence for histamine as key regulator in the envenomation by caterpillar Automeris zaruma - Seldeslachts, Andrea; Peigneur, Steve; Mebs, Dietrich; Tytgat, Jan (Frontiers in Immunology, 2022)
Over the past decades, envenomation by caterpillars of Automeris spp. became an increasing health problem in Latin America. Accidental contact with the stinging spines of these caterpillars cause acute local pain, itching, inflammation and skin rashes that persists for days. Even when the cause is obvious, the exact molecular mechanisms responsible for the observed symptoms are yet to be elucidated. Here, we describe for the first time, an active compound in the venom and the study of the bioactivity of the venom extracted from the spines of the caterpillar Automeris zaruma. Electrophysiological screening of a library of membrane proteins important for pain and itch enabled us to investigate and reveal the mode of action of the venom of A. zaruma. Further mass spectrometric analysis (Q-TOF-MS) made it possible to establish a link between the bioactivity and the components found in the venom. We show that the spine extract of A. zaruma contains histamine that potently activates the four types of the human histamine receptors (H1R, H2R, H3R and H4R) with a selectivity preference towards H3R and H4R. Furthermore, a modulation of the target MRGPRX2 was found. Together, these findings are the first to explain the symptomology of A. zaruma envenomation, enabling us a better understanding of caterpillar envenomation and predict that the hurdle of the scarce efficacy of the currently used antihistaminic drugs can be overcome by including H3R and H4R blockers in the clinical used medication. Such an approach might be used for other caterpillar envenomation in the world and represent a significant improvement for the well-being of the patient.